Impact of different cropping sequences on the population density of phytoparasitic nematodes in the farmer's field - SHARMA*, G.C. (Indian Phytopathology, 2007)
In the farmer's field, four cropping sequences were studied for their impact on the populations of prevalent phytoparasitic nematodes. Different crops involved in the sequences were; mustard, tomato, maize, wheat, onion, gram, ginger and pea. Against root-knot nematode problem (which is very serious in Kharif vegetables), crops like pea, wheat and maize proved beneficial. Fields with spiral nematode (Helicotylenchus species) problem, cultivation of the crops like tomato and gram may be advisable. Against lesion nematode (Pratylenchus species), crops like tomato, onion and pea were found to be of high significance. Cultivation of onion can also be suggested in the fields harbouring high population densities of stunt nematode (Tylenchorhynchus species). Onion was the crop which did check the overall phytoparasitic nematode populations.